FAKTOR-FAKTOR MEMPENGARUHI KETIDAKPATUHAN MINUM OBAT ANTI TUBERKOLUSIS PADA PASIEN TB PARU DI PUSKESMAS GEMBOR KOTA TANGERANG - lastri mei winarni; abdul santoso; nurul indah savitri (Universitas Yatsi Madani, 2019)
Background: The results of preliminary study at Puskesmas Gembor in 2016 there are 65 people with TB and in 2017 there are 71 people with TB, increasing TB patient equal to 9,2%. Caused due to one factor of non-compliance to take medication for 65% of patients with pulmonary TB. Objective: The purpose of this study was to determine the factors that influence disobedience of taking pulmonary TB drugs with the incidence of pulmonary TB in Puskesmas Gembor. Research Methods: The type of research used descriptive with the method is quantitative. The number of samples in this study was 71 people. Analytical technique used univariate to obtain the characteristics of each demographic variables and bivariate used to determine the relationship between research variables. Result: Based on the analysis result, is 1) No relationship between Age with disobedience taking anti-tuberculosis drug with P-value of 0,589; 2) There is no correlation between education with disobedience taking anti-tuberculosis drugs with P-value 0,427, 3) No relationship between occupation with disobedience anti-tuberculosis drugs with P-value of 0, 605; 4) There is a correlation between Health Facilities with disobedience taking anti-tuberculosis drugs with P-value of 0.040; 5) There is a relationship between family support and disobedience of taking anti-tubercolosis drugs with P-value of 0,030; 6) There is correlation between health officer attitude with disobedience of taking anti tuberculosis drugs in TB patient at Puskesmas Gembor Tangerang in 2018 with P-value program of equal to 0,008. Suggestion: It is expected that health workers managing the treatment and control taking drugs anti Tuberculosis (TBC), to provide support to the family in order to constantly control the obidience of taking anti tuberculosis drugs for tht patiens in order to prevent drug break and resistance